PROBLEMS IN PSYCOLOGICAL EXPERT EXAMINATION OF CIVIL CASES - Arakelyan , A. D.; Sargsyan , L. K. (Modern Psychology, 2022)
The paper attempts at presenting the existing problems in the field of forensic psychological examinations in civil cases, which complicate, and in some cases hinder the effective process of psychological examinations. In particular, the paper discusses legal and psychological grounds for appoint- ting a forensic psychological examination in civil cases, professional uncer- tainties in the examination questions, existing difficulties and issues related to their solution as well as involvement of the parties in the examination.